2016
DOI: 10.1088/0957-4484/27/45/455604
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth mechanism of poly (3-hexylthiophene) nanowires

Abstract: Synthesis of 1D-polymer nanowires by a self-assembly method using marginal solvents is an attractive technique. While the formation mechanism is poorly understood, this method is essential in order to control the growth of nanowires. Here we visualized the time-dependent assembly of poly (3-hexyl-thiophene-2,5-diyl) (P3HT) nanowires by atomic force microscopy and scanning tunneling microscopy. The assembly of P3HT nanowires was carried out at room temperature by mixing cyclohexanone (CHN), as a poor solvent, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
(37 reference statements)
0
25
0
Order By: Relevance
“…Also, mixtures of good and poor solvents have the capacity to generate a larger yield of aggregates than pure marginal solvents, which may impose limitations on the latter toward certain applications, such as optimizing the doping efficiency of P3HT . Despite these advantages of solvent mixtures, the available literature on the assembly and crystallization of P3HT in solvent mixtures is rather scarce, compared to those involving pure solvents . Furthermore, most of these endeavors exploit the fabrication of P3HT aggregates as a means to (1) manipulate the morphology of films and P3HT/nanoparticle composites, (2) affect charge transport and field effect mobility, or (3) study the structure and photophysics of the aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Also, mixtures of good and poor solvents have the capacity to generate a larger yield of aggregates than pure marginal solvents, which may impose limitations on the latter toward certain applications, such as optimizing the doping efficiency of P3HT . Despite these advantages of solvent mixtures, the available literature on the assembly and crystallization of P3HT in solvent mixtures is rather scarce, compared to those involving pure solvents . Furthermore, most of these endeavors exploit the fabrication of P3HT aggregates as a means to (1) manipulate the morphology of films and P3HT/nanoparticle composites, (2) affect charge transport and field effect mobility, or (3) study the structure and photophysics of the aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Kiymaz et al reported a similar trend from high aspect ratio fibers to in P3HT films prepared at multiple time intervals after adding the poor solvent, cyclohexanone, to a P3HT:chlorobenzene solution (see Figure in ref. ).…”
Section: Resultsmentioning
confidence: 97%
“…In this context, the mixing kinetics can modulate the assembly process in such a way that small amounts of fibrous aggregates are fabricated in the 70:30 CF:HEX FAC samples. This supposition is consistent with the fact that the fibrous features in the film are observed when we used the smaller diameter vial and supports the claim by Kiymaz et al, that the thickness of P3HT nanowires is dictated by the “nanowire creation velocity.”…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such understanding would also help in creating ideas to control defects and in this way to prepare 2DMs with novel properties. Point defects, including vacancy, impurity, adsorption, and substitution of atoms and different methods such as strain engineering and applying an electric field can tailor the electronic properties of 2DMs, can be used for a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%